2008
DOI: 10.1111/j.1440-1827.2008.02320.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic strategy targeting the mTOR–HIF‐1α–VEGF pathway in ovarian clear cell adenocarcinoma

Abstract: Malignant tumors usually involve a relatively hypoxic state, which induces overexpression of hypoxia-inducible factor-1alpha (HIF-1alpha) to satisfactorily enable the tumor to survive. Thus, inhibition of the mammalian target of rapamycin (mTOR) pathway including HIF-1alpha is expected to play a major role in suppression of tumor cell growth, having recently drawn much attention as an anti-cancer therapeutic strategy for various malignant tumors. In the present study, which compared clear cell adenocarcinoma (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 43 publications
2
56
1
1
Order By: Relevance
“…It is known that mutations of PIK3CA are common molecular genetic alterations identified in OCCC (11). Expression of phospho-mTOR was found to be more prominent in OCCC than in OSAC (22). mTOR exists in two distinct complexes, mTOR complex 1 (mTORC1) and mTORC2.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that mutations of PIK3CA are common molecular genetic alterations identified in OCCC (11). Expression of phospho-mTOR was found to be more prominent in OCCC than in OSAC (22). mTOR exists in two distinct complexes, mTOR complex 1 (mTORC1) and mTORC2.…”
Section: Discussionmentioning
confidence: 99%
“…This HIF-1α-mediated expression of VEGF may be an important mechanism regulating luteal development and function in the mammalian ovary. HIF-1α antagonism may be useful for the development of novel treatments for fertility control and for certain types of ovarian dysfunction (11,43,46), particularly those conditions characterized by pathological angiogenesis and excessive vascular permeability, including polycystic ovarian syndrome, ovarian hyperstimulation syndrome and ovarian neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1, a helix-loop-helix transcriptional factor, which consists of HIF-1α and HIF-1β, has been cloned and characterized as a transcriptional activator of several oxygen-sensitive genes, including erythropoietin, heme oxygenases, transferrin and several glycolytic enzymes (27)(28)(29)40), whose protein products are important in developmental and physiological processes, including angiogenesis, erythropoiesis, glycolysis, iron transport and cell proliferation/survival (2,5,11,(41)(42)(43). It has been reported that HIF-1α protein is inducible by a decrease of O 2 concentration in tissue or cells.…”
Section: Discussionmentioning
confidence: 99%
“…In transgenic (orthotopic) and xenograft mouse models, treatment with the mTOR inhibitor everolimus delayed tumor development, reduced tumor burden, and prolonged survival (9)(10)(11)(12). mTOR inhibition reduced VEGF-A expression and diminished vascularization in murine (xenograft) ovarian cancers (9,10).…”
Section: Introductionmentioning
confidence: 99%